Effectiveness of hand cooling and a cooling jacket on post-exercise cooling rates in hyperthermic athletes - Maroni, T.; Dawson, B.; Barnett, K.; Guelfi, K.; Brade, C.; Naylor, L.; Brydges, C.; Wallman, K. (European Journal of Sport Science, 2018)
This study compared the effects of a hand cooling glove (~16°C water temperature; subatmospheric pressure of -40 mmHg) and a cooling jacket (CJ) on post-exercise cooling rates (gastrointestinal core temperature, Tc; skin temperature, Tsk) and cognitive performance (the Stroop Colour-Word test). Twelve male athletes performed four trials (within subjects, counterbalanced design) involving cycling at a workload equivalent to 75% O2max in heat (35.7 ± 0.2°C, 49.2 ± 2.6% RH) until a Tc of 39°C or exhaustion occurred. A 30-min cooling period (in 22.3 ± 0.3°C, 42.1 ± 3.6% RH) followed, where participants adopted either one-hand cooling (1H), two-hand cooling (2H), wore a CJ or no cooling (NC). No significant differences were seen in Tc and Tsk cooling rates between trials; however, moderate effect sizes (d = 0.50-0.76) suggested Tc cooling rates to be faster for 1H, 2H and CJ compared to NC after 5 min; 1H and CJ compared to NC after 10 min and for CJ to be faster than 2H at 25-30 min. Reaction times on the cognitive test were similar between all trials after the 30 min cooling/no-cooling period (p > .05). In conclusion, Tc cooling rates were faster with 1H and CJ during the first 10 min compared to NC, with minimal benefit associated with 2H cooling. Reaction time responses were not impacted by the use of the glove(s) or CJ.